(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Second Language Acquisition (SLA) is a complex process through which learners acquire a language other than their native language. The success of language learning depends on cognitive, social, and affective factors that influence how learners process and produce the target language. This article explores the main principles of SLA and provides strategies for creating exercises that facilitate both comprehension and production. Key SLA theories, including Krashen’s Input Hypothesis, Swain’s Output Hypothesis, and Long’s Interaction Hypothesis, are discussed in detail.